Epigenetic factors in posttraumatic stress disorder resilience and susceptibility - Tamer A. Addissouky; Ibrahim El Tantawy El Sayed; Yuliang Wang (Egyptian Journal of Medical Human Genetics)
Abstract Background Posttraumatic stress disorder (PTSD) affects approximately 8% of the US population, with varying susceptibility among individuals exposed to trauma. While genetic factors contribute to PTSD risk, emerging evidence suggests that epigenetic mechanisms play a crucial role in translating environmental exposures into lasting neurobiological changes. Purpose This review provides a comprehensive analysis of cutting-edge research on epigenetic factors in PTSD, with particular emphasis on novel findings regarding resilience and susceptibility mechanisms. We explore recent technological advances in epigenetic research and their applications in understanding PTSD pathophysiology. Main body Advanced epigenomic approaches have revealed complex interactions between DNA methylation, histone modifications, and non-coding RNAs in PTSD. Novel findings highlight cell type-specific epigenetic signatures and their temporal dynamics following trauma exposure. Single-cell epigenomic studies have identified previously unknown cellular heterogeneity in stress responses. Recent data suggests that epigenetic modifications not only influence individual susceptibility but may also contribute to transgenerational transmission of trauma effects. Integrative multi-omics approaches have revealed new insights into the molecular networks underlying PTSD resilience and vulnerability. Conclusion Recent technological advances in epigenetic research have revealed unprecedented complexity in the molecular mechanisms of PTSD. These findings open new avenues for personalized interventions based on individual epigenetic profiles and suggest novel therapeutic strategies targeting epigenetic modifications. This enhanced understanding of epigenetic factors in PTSD has significant implications for risk assessment, prevention, and treatment. Graphical abstract